Civil society's view about Turkey's migration and asylum policy and Syrian refugee crisis : sivil toplumun Türkiye'nin göç ve iltica politikası ve Suriye mülteci krizine bakışı - Rozsypalova, Anna (My University, 2018)
Bu çalışma, mülteci hareketinin ev sahibi devlet ve nüfusunun üzerindeki etkileriyle alakalı karmaşık soruları, ve ev sahibi ülkeye doğru gerçekleşen beklenmedik “mülteci” akınıyla ilgili soruları, bir sosyal bilimcinin tarafsız bakış açısıyla ele almayı ve incelemeyi hedeflemektedir. Daha somut bir ifadeyle çalıĢmanın konusu, 2011-2013 yılları arasında Türkiye‟de kademeli olarak gelişen Suriye mülteci meselesinin genel niteliğini analiz etmektir. Özellikle mülteci statüsü verilmesi yerine Suriyelilerin geçici koruma altına alınması, bu politik adımın yasallığı açısındançok tartıĢmalı bir konu. Öte yandan, Türkiye‟nin göç ve iltica sisteminin genel reformunun da Suriyeliler üzerinde çok olumlu bir etkisi olduğu kabul edilmelidir. Bu kapsamda, Yabancılar ve Uluslararası Koruma Kanunu‟ndan bahsetmek gerekir. Araştırma teorik ve pratik olmak üzere iki bölümden oluşmaktadır. Teorik bölüm; Türkiye‟nin göç ve iltica sisteminin tarihine ve Suriyeli mülteciler konusuna odaklanmaktadır. Tabi ki teorik bölümün yukarıda söz edilen iki konuyla ilgili akademik tartıĢmaları yansıtması amaçlanmaktadır. Son olarak, çalışmanın esas bölümü, sivil toplum temsilcileriyle şahsen yapılan görüşmelere dayanan pratik kısımdır. Bu bölüm, Türkiye‟deki sivil toplumunun Suriyeli mülteci meselesi hakkındaki genel algısını yansıtmayı hedeflemektedir. Elbette ki pratik bölümün sorunla ilgili daha derin bir kavrayış kazandırması ve sivil toplumu çözüm bulma sürecine dahil etmesi planlanmaktadır. Ayrıca bu bölüm, Türk sivil toplum temsilcilerine meseleye bakıĢlarını ifade etme imkanı vermeyi ve Türkiye‟deki Suriyeli mülteciler sorununa sürdürülebilir ve dengeli çözüm bulmada bir ön koĢul olan ulusal bir diyaloğa katkıda bulmayı amaçlamaktadır.

The aim of the research is to examine the complex questions related to the impacts of the refugee movement on the host state and its population from a neutral point of view of a social scientist and to address the crucial questions which arise as a result of a sudden, unexpected mass influx of refugees into the host country.More concretely, the research work is supposed to analyse the overall nature of the Syrian refugee issue in Turkey which has gradually evolved since 2011, 2012-2013 respectively. Particularly the fact that Syrians have been placed under temporary protection, instead of being granted a proper refugee status, is a very disputable issue raising a wide range of questions over the legality of this political step. Meanwhile, it must be acknowledged that the overall reformation of Turkey´s migration and asylum system has had a very positive impact on Syrians as well. In particular, the introduction of the Law on Foreigners and International Protection is worth appraisal.The research is composed of two parts, i.e. the theoretical and the practical one. The theoretical part is the outcome of the academic researches focusing on the history of Turkey´s migration and asylum system, and the Syrian refugee issue respectively. Indeed, the theoretical part is supposed to mirror general academic reflections on the two above mentioned subjects.The prior attention should be drawn particularly to the second, i.e. the practical part which is based on the interviews personally conducted with the representatives of the civil society.In comparison to the first part, the practical part is aimed to mirror general perception of Turkish civil society with regards to the Syrian refugee issue. Indeed, the practical part is supposed to intermediate a more in-dept insight into the question and to involve the civil society in the solutionfinding process. Moreover, the aim of the practical part is to let the representatives of Turkish civil society express their points of view and to contribute to a national dialogue which, in fact, is a precondition for finding a balanced and sustainable solution to the Syrian refugee issue in Turkey.
Keywords: a host state; civilsociety; Devlet politikası; Emigration and immigration; ev sahibi devlet; geçici koruma; Government policy; Göç ve göçmenlik; göç ve ilticapolitikası; mass influx; migration and asylum policy; mülteci akını; mülteci statüsü; Mülteciler; Mülteciler, Suriyeli; Non-governmental organizations; Refugees; Refugees, Syrian; refugeestatus; Sivil toplum örgütleri; Suriye; Suriye “mülteci” krizi; Syria; Syrian refugee crisis; temporary protection; the Law on Foreigners and International Protection; Turkey; Türk sivil toplumu Turkey; Türkiye; Yabancılar ve Uluslararası Koruma Kanunu